Case study: Patterson Irrigation District's use of SCADA for total water & energy management - Sweigard, John, author; Hearth, Dick, author; Crossett, Mark, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2002)
Making accurate, informed operational decisions in water and energy management can have significant resource and fiscal impacts on irrigation districts. The need for accurate and reliable real-time and historical data is key in making these vital decisions. The use of every acre-foot of water and every kilowatt-hour of energy, resource management, has become the topic of scrutiny in today's world. The protection of these valuable water and energy resources, held in trust and managed by the irrigation district, on behalf of its' landowner constituents, is one of the vital functions of the Patterson Irrigation District (PIO). Plant Control and Supervisory Control and Data Acquisition (SCADA) systems can provide the link between data and effective District operations and management. This case study will outline the initial development, expansion and subsequent upgrade of the Patterson Irrigation District's Plant Control and SCADA systems, the role in data acquisition and daily district operations, the benefits the district and its water users have accrued from accurate real-time and historical data and finally, the lessons learned in the development, implementation and evolution of a state-of-the-art Plant Control and SCADA system for irrigation district use. In its first full year of operation, 1999, historical data verified an increase of 23% in total Station #1 pumping plant efficiency on a kW-hr per acre-foot basis.
USCID/EWRI conference
Patterson Irrigation District
Not digitized by CSUL Digital Services.
Presented at the 2002 USCID/EWRI conference, Energy, climate, environment and water - issues and opportunities for irrigation and drainage on July 9-12 in San Luis Obispo, California.